Translating English WOMAN IS AN ANIMAL metaphors: Spanish native speakers’ associations with novel metaphors - Fernandes, Kristina (Linguistik Online, 2021)
Animal metaphors are prevalent across languages and convey a variety of, oftentimes negative, meanings – more so for women than men. In English, for example, both lion and lioness refer to a sexually active, dominant man or woman respectively, but while the former is endowed with positive connotations (courage, strength), the latter evokes negative associations (danger, voracity). There are some animal terms, however, that do not feature in animal metaphors in a certain language, posing the question as to which associations are evoked by those animal terms that are not part of conventional animal metaphors. This paper explores Spanish speakers’ interpretations of mappings of the woman is an animal metaphor that are documented to exist in English but not in Spanish. This was tested with two online questionnaires, one employing open questions and the other one Likert scales presenting possible traits (e. g. quarrelsome, kind, promiscuous), in which Spanish speakers had to judge the animal metaphors which were translated from English. The results show that the novel animal metaphors are mainly associated by Spanish native speakers with negative features, first and foremost with ugliness. Additionally, most of the animal terms convey different meanings in English and Spanish. For example, musaraña, the Spanish equivalent of shrew, is not associated with bad temper and quarrelling, but instead with ugliness and muddleheadedness. Furthermore, the findings reveal significant insecurities in the interpretation of the translated metaphors by the Spanish speakers. These results might be an indication for both the arbitrariness and the stableness of associations with different animal species, depending on the speakers’ culture. It also seems that novel animal metaphors mainly provide mental access to unattractiveness as it is a concrete physical feature and might therefore be more accessible than abstract personality traits such as kindness or quarrelsomeness.